UPAYA MENINGKATKAN KETERAMPILAN MENGAJAR GURU MATEMATIKA SD DALAM MERANCANG PEMBELAJARAN BERBANTUAN ALAT PERAGA MELALUI BIMBINGAN BERKELOMPOK - Ernalis Ernalis (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is motivated by the learning carried out by teachers is less attractive to elementary school students, resulting in student learning outcomes being low. The purpose of this study is to improve teacher teaching skills in designing teaching aids assisted by group guidance. This research is a school action research conducted at the Lubuk Batu Jaya sub-district target schools. The implementation of this study began February 18 to April 27, 2019. The subjects of this study were 4 groups of Mathematics teachers. Data analysis techniques are carried out through steps: data reduction, data presentation, verification. The results of the study showed an increase from cycle I to cycle II with the percentage and each category being 62% (sufficient) and 73% (good). The conclusion that can be drawn is that the teaching skills of elementary school mathematics teachers in designing learning assisted by teaching aids have increased after group guidance was carried out.